To calculate the simple interest earned by Lisa each year, we use the formula: Interest = Principal * Rate * Time.
For the first year:
Interest_Lisa_Year1 = $10,000 * 6% * 1 = $600.
For the second year:
Interest_Lisa_Year2 = $10,000 * 6% * 1 = $600.
For the third year:
Interest_Lisa_Year3 = $10,000 * 6% * 1 = $600.
Therefore, Lisa earns $600 in interest for each of the first three years.
To calculate the compound interest earned by Scott each year, we use the formula: Compound Interest = Principal * (1 + Rate)^Time - Principal.
For the first year:
Compound_Interest_Scott_Year1 = $10,000 * (1 + 6%)^1 - $10,000 = $600.
For the second year:
Compound_Interest_Scott_Year2 = $10,000 * (1 + 6%)^2 - $10,000 = $636.
For the third year:
Compound_Interest_Scott_Year3 = $10,000 * (1 + 6%)^3 - $10,000 = $676.16.
Therefore, Scott earns $600, $636, and $676.16 in compound interest for the first, second, and third years, respectively.
Comparing the interest earned by Lisa and Scott each year:
Year 1: Lisa earns $600 in simple interest, while Scott earns $600 in compound interest. They both earn the same amount.
Year 2: Lisa earns $600 in simple interest, while Scott earns $636 in compound interest. Scott earns more interest.
Year 3: Lisa earns $600 in simple interest, while Scott earns $676.16 in compound interest. Scott earns more interest.
In conclusion, Scott earns more interest than Lisa for the second and third year when considering compound interest. For the first year, they both earn the same amount of interest.
Lisa deposits $10,000 into an account that pays simple interest at a rate of 6% per year Scott deposits $10,000 into an account that also pays 6% interest per year but it is compounded annually find the interest Lisa and Scott earned during each of the first three years then decide who earns more interest for each year assume there are no withdrawals and no additional deposits
1 answer